Single shot and speckle free reconstruction of orthogonal polarization modes with a tuneable beam displacer - Manisha; Rathor M.; Singh R.K. (My University, 2025)
Imaging through a random scatterer is a challenging problem due to the spatial scrambling of the light wavefront and formation of the speckle pattern. Here, we present a new experimental configuration in holography with a two-point intensity correlation to reconstruct the orthogonal polarization modes from a single shot measurement of the speckle pattern. Speckle free orthogonal polarization modes are reconstructed by applying the ensemble averaging in the correlation analysis. Both orthogonal polarization components of the object are simultaneously reconstructed using an edge point referencing for holography with the coherence waves and with a specially designed tuneable beam displacer. This tuneable beam displacer supports independent recording of the orthogonally polarized speckles at different spatial locations, and hence supports simultaneous reconstruction of the orthogonal polarization components of object from the random light. © 2022 IOP Publishing Ltd.